Urinary Cadmium and Cotinine Levels and Hair Mercury Levels in Czech Children and Their Mothers Within the Framework of the COPHES/DEMOCOPHES Projects - Forysová, Kateřina; Pinkr-Grafnetterová, Anna; Malý, Marek; Krsková, Andrea; Mráz, Jaroslav; Kašparová, Lucie; Čejchanová, Mája; Sochorová, Lenka; Rödlová, Sylva; Černá, Milena (Archives of environmental contamination and toxicology, 2017)
The COPHES/DEMOCOPHES twin project was performed in 2011-2012 in 17 European countries to harmonize all steps of the human biomonitoring survey. Urinary cadmium, cotinine, phthalate metabolites, and hair mercury were measured in children (N = 120, 6-11 years) and their mothers of reproductive age, living in urban or rural areas. Cadmium in mothers' and children's urine was detected at a geometric mean (GM) concentration 0.227 and 0.109 μg/L, respectively; 95th percentile (P95) was 0.655 and 0.280 μg/L in mothers and children, respectively. No age-related, education-related, or urban versus rural differences were observed within the frame of each population group. Cadmium urinary level in mothers was about twofold compared with children. Higher levels were obtained in all smoking mothers but not in occasionally smoking or mothers and children exposed to environmental tobacco smoke (ETS). Mercury values in mothers were significantly higher in urban than in rural populations but not in children. GM and P95 for mercury in children's hair were 0.098 and 0.439 μg/g and in mothers' hair were 0.155 and 0.570 μg/g. Concentrations for mercury in the Czech samples were lower than European average. Hair mercury increased significantly with consumption of fish or seafood and with number of amalgam tooth fillings (in children). A positive association was found with family educational level. No influence of age was observed. Urinary cadmium and hair mercury levels were lower than health-based guidelines with one exception. High levels of urinary cotinine were found in the 12 smoking mothers (GM approximately 500 μg/L); lower levels in occasionally smoking mothers, N = 11 (34.5 μg/L). The mean cotinine levels in nonsmoking mothers who reported daily exposure to ETS was 10.7 μg/L. A similar mean value (10.8 μg/L) was obtained in six children who had daily exposure to ETS. In children without exposure to ETS, the mean cotinine level was 1.39 μg/L urine. Cotinine in the urine of children demonstrates limited protection of the Czech children against exposure to ETS.
Keywords: Maternal Exposure; Environmental Exposure; vlasy, chlupy; látky znečišťující životní prostředí; Adult; vystavení vlivu životního prostředí; Geometric Mean; lidé; Humans; Cadmium; Child; matka - expozice noxám; kadmium; Cotinine Level; Cotinine; Czech Republic; Mothers; kotinin; Environmental Tobacco Smoke; dospělí; Hair; dítě; matky; Environmental Tobacco Smoke Exposure; Česká republika; ženské pohlaví; Female; Environmental Pollutants